Model Pembelajaran Concept Attainment Terhadap Kemampuan Berpikir Kreatif Pada Materi Bangun Ruang Siswa Sekolah Dasar - Ananda, Firta; Rosimanidar, Rosimanidar; Akmal, Nurul (Universitas Muhammadiyah Magelang, 2025)
The main objective of this study was to determine how the Concept Attainment learning model affects students’ creative thinking ability in learning three-dimensional geometry in Grade V at SDN 3 Geureudong Pase. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 42 students, with 21 students from class V-A and 21 students from class V-B. Purposive sampling was used to select the sample. The research instrument was an essay test. Using SPSS 25, the results showed that both the experimental and control groups obtained a Sig. (2-tailed) value of 0.249 > 0.05, indicating that the Concept Attainment learning model has an effect on students’ creative thinking ability. Furthermore, the basic linear regression test revealed an R Square value of 0.348, indicating that the independent variable Concept Attainment learning model influenced the dependent variable (creative thinking ability) by 34.8%. Given that the significance value obtained was 0.005 < 0.05, it can be concluded that the Concept Attainment learning model significantly affects students’ creative thinking ability in learning three-dimensional geometry for Grade V at SDN 3 Geureudong Pase.